Asymmetric Effects of Financing Models on Islamic Rural Bank Profitability: The Moderating Role of Socioeconomic Factors and Credit Risk - Akbar Surya Maulana; Titis Miranti; Yenny Kornitasari (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2026)
This study aims to analyse the impact of Profit and Loss Sharing (PLS) and Non-PLS financing on the profitability of Rural Islamic Banks (BPRS) in Indonesia, incorporating Non-Performing Financing (NPF), financial literacy, and the inequality index as moderating variables. A quantitative approach is employed, utilizing panel data from BPRS for the period 2011–2024, which includes 644 observations from 44 BPRS in Indonesia. The analysis is conducted using panel data regression and Moderated Regression Analysis (MRA). The findings reveal that PLS financing exerts a positive and significant effect on profitability, whereas non-PLS financing does not exhibit a significant effect. NPF moderates the relationship between PLS financing and profitability in a strengthening manner, while it moderates non-PLS financing in a weakening manner. Financial literacy does not moderate the relationship between PLS financing and profitability, but it diminishes the effect of non-PLS financing on profitability. The inequality index does not moderate PLS financing but reduces the effect of non-PLS financing on profitability. These results suggest that PLS financing is instrumental in maintaining the sustainability of BPRS. Additionally, PLS financing serves as a source of working capital for productive business customers, thereby enhancing the profitability of BPRS.